KEBIJAKAN PENGELOLAAN PULAU KECIL PERBATASAN BERBASIS GEOPOLITIK, DAYA DUKUNG EKONOMI DAN LINGKUNGAN (Kasus Pulau Pulau Kecil Perbatasan Kepulauan Sangihe, Sulawesi Utara) - Achmad Nasir Biasane; Akhmad Fauzi; Daniel R. Monintja; Dedi Soedharma (Fakultas Perikanan dan Ilmu Kelautan, 2011)
Execution of Sipadan and Ligitan islands by International Court of Justice as the part of sovereignity of Malaysia based on effective occupation, have encouraged Indonesia to be more aware and care for developing the neighboring state small islands. There are many national and regional institutions have developed programs and activities for the neighboring state small island but the programs still sector and partial oriented, whereas no national policy yet concerning the neighboring state small islands management. This research was to formulate comprehensive policy for the management of neighboring state small islands of Sangihe archipelago based on geo-politic, economic and environment carrying capacity. Specific objective were: (1) to evaluate and formulate of management policy for neighboring small islands of Sangihe archipelgo based on geo-politic, and (2) to evaluate economic and environment carrying capacity for formulate input of neighboring small islands management policy in Sangihe Archipelagic. The research was conducted Archipelagic in Regency of Sangihe, North Sulawesi Province. Primary data collected at Tahuna, Marore Island, Matutuang Island, Tinakareng Island, and Kawio Island. Secondary data collected since proposal developing until data analysis. Results of the study show that the potential sectors to be developed for Sangihe are capture fisheries and estate commodities. This research to develop of capture fisheries on analysis, basically the scads fish (Decapterus sp.), trvevallies (Selar spp.), eastern little tuna (Euthynus sp.), skipjack tuna (Katsuwomus pelamis), shark (Charcarias sp.) and tuna (Thunnus albacares). The average sustainable production of the scad fish 20 years (1988-2007) observation 1s 1746,3 tons/year, trevallies is 194,1 tons/year, sharks is 148,4 tons/year, skipjack tuna is 315,6 tons/year, tuna is 152 tons/year, and estern little tuna is 1073,2 tons/year on the same period. The priorities of neighboring small island policies are: (1) development of capture fisheries, coconut and nutmeg estate; (2) demarcation and delimitation of boundary state; (3) develop system of defence and security in the neighboring state small islands; (4) the change of agreement of border trade base on economic value; and (5) optimal and sustainable utilization of natural resource.